Distribution and nymphal age of Dinocras cephalotes (Curtis) (Plecoptera: Perlidae) in northern Finland - Erkinaro, Heikki; Erkinaro, Jaakko (Entomologica Fennica, 2003)
The largest species of Scandinavian plecopterans, Dinocras cephalotes (Curtis), was identified in the River Inarijoki, northern Finnish Lapland in 1990, being the first record of this species in Finland. In spite of the widespread zoobenthos survey carried out in all major river systems in the northernmost Lapland, the distribution of D. cephalotes seems to be restricted to a small geographical area in the R. Inarijoki, which forms part of the border between northern Norway and Finland. The nymphal stage of D. cephalotes appears to take four years in northern Finland, and no indications of a five-year nymphal stage, earlier suggested for northernmost Scandinavia, were found.